#TITLE_ALTERNATIVE# - IMADUDDIN (NIM 10101004), KHOLIS
In this final project, the solution of the rubik's magic cube will be inquired using group theory. At the solved state, all the same colored facelets reside at the same side of the rubik's cube. The jumbled state of rubik's cube will be viewed as a result of the action of an element of a group on the facelets of the solved rubik's cube. The group involved in this matter is the facelets' permutation group, which is generated by the action of rubik's face turn on the facelets . The properties of that group will then be studied by looking at its action toward the resulting position and orientation of the cubies. This knowledge will then be used as a guidance into the method of solution.